Peningkatan Motivasi dan Hasil Belajar Siswa Melalui Pendekatan SETS Pada Materi Pencemaran Lingkungan Kelas VII E SMP Negeri 1 Wonosari - Iin Indriyati (Ideguru: Jurnal Karya Ilmiah Guru, 2019)
This class action research aims to improve students' motivation and learning outcomes through the SETS (Science, Environment, Technology and Society) approach to Environmental Pollution VII VII E material, SMP Negeri 1 Wonosari in semester 2 academic year 2017/2018. This research lasted for 2 (two) cycles, the first cycle was held 3 (three) meetings and the second cycle was held 2 (two) meetings. Things to be improved through this classroom action research are learning motivation and student learning outcomes through the SETS approach. Data collection techniques used were questionnaires and tests. Motivation questionnaire data is in the form of student acquisition scores during cycle I and cycle II while the learning outcome data is the value of student test results after the learning process of cycle I and cycle II. The results of the questionnaire are tabulated and processed and then compared with indicators of success that have been determined to measure the improvement and achievement. The test result data is processed by calculating the percentage of students who reach the KKM then compared with indicators of success to find out the improvement and achievement. Based on the results of data analysis and discussion it can be concluded that the SETS approach can increase student motivation and student learning outcomes. The final recapitulation of student learning motivation increased from 65.83% (enough) in the first cycle to 76.28% (good) in the second cycle while the student learning outcomes increased from 58.33% in the first cycle to 83.33% in the second cycle.